Fahr syndrome and neurological manifestations in hypoparathyroidism patients - Vincentius Diamantino Supit, MD; Dedy Kurniawan, MD; Ersifa Fatimah, MD (Radiology Case Reports, 2024)
Fahr syndrome is an uncommon (prevalence < 1/1.000.000) neurological disorder characterized by abnormal calcified deposits in the basal ganglia, nucleus dentatus, and cerebral cortex. These calcification can lead to various neurological manifestations. Distinguishing Fahr syndrome from Fahr disease is crucial due to differences in their etiology, location of lesions, prognosis, and therapy. Currently, Fahr disease lacks a specific treatment, while Fahr syndrome requires target intervention based on the underlying cause. A 35 years old female patient was presented to the emergency department with recurrent tonic-clonic seizures followed by the decreased consciousness. The patient had history of thyroidectomy surgery 7 years before, behavioral disturbances, hallucinations for past 1 week, and cataracts in both eyes. Laboratory examination showed low calcium levels (4 mg/dL), which can trigger seizures, and low PTH levels, indicating hypoparathyroid. A head CT scan without contrast displayed extensive bilateral calcification, particularly in the basal ganglia. Following stabilization, an EEG recording discovered diffuse encephalopathy. The patient received seizure management and maintenance medication of calcium with vitamin D. During the 3 months follow up, no sign of relapses were observed. Intracranial calcifications are often physiological but should be suspected as pathology in certain symptoms and calcification patterns. The presence of multiple intracranial calcifications, specifically in the basal ganglia, indicates Fahr disease or Fahr syndrome, which can cause various neurological manifestations. One of the etiologies of Fahr syndrome to consider is hypoparathyroid. Therefore, identifyisng and managing this etiology is crucial for preventing the progression of Fahr syndrome.